Case report: A rare DLST mutation in patient with metastatic pheochromocytoma: clinical implications and management challenges - Li, Chang; Han, Liang; Song, Yuming; Liu, Rui (Frontiers in Oncology, 2024)
Background Pheochromocytoma is one of the most hereditary human tumors with at least 20 susceptible genes undergoing germline and somatic mutations, and other mutations less than 1% -2%. In recent years, other rare mutations have gradually been discovered to be possibly related to the pathogenesis and metastasis of pheochromocytoma. Most patients with pheochromocytoma experience common symptoms like headaches, palpitations, and sweating, while some may have less common symptoms. The diversity of symptoms, genetic mutations, and limited treatment options make management challenging. Case presentation A 53-year-old woman was hospitalized after experiencing episodic epigastric pain for one month. A mass was found in her right adrenal gland and she underwent robot-assisted laparoscopic surgery, revealing a pheochromocytoma. At the 16-month follow-up, multiple metastatic lesions consistent with metastatic pheochromocytoma were found. A germline mutation in the dihydrolipoamide succinyltransferase (DLST) gene (c.330 + 14A>G) was detected, and despite trying chemotherapy and adjuvant therapy, the patient had a limited response with an overall survival of 27 months. Conclusions DLST mutation is one of the rare pheochromocytoma-related mutated genes, and genetic sequencing is crucial for effective clinical management.